Elaboração de uma história infantil como recurso para a abordagem dos elementos essenciais da Tabela Periódica - Ribeiro, Rhayana Vitória (Universidade Federal de São Carlos, 2025)
This work aims to develop a children's story as a didactic resource to address the essential elements of the Periodic Table, contributing to the scientific literacy of children in elementary school. The narrative "The Journey on Planet Sigma" adopts a playful and interdisciplinary approach, in which the characters experience adventures in search of the elements Carbon, Hydrogen, Oxygen, Nitrogen, Phosphorus, and Sulfur — substances fundamental to life. The research is qualitative in nature, based on the scientific literacy indicators of Pizarro (2023, pp. 26 and 27) and the guidelines of the National Common Curricular Base (BNCC, 2018). The proposed resource seeks to stimulate curiosity and scientific reasoning, bringing chemical concepts closer to children's daily lives through creative and accessible language. It is hoped that the proposal will contribute to the development of innovative pedagogical practices that make science teaching more attractive, formative, and meaningful from childhood.
Creating a children's story as a resource for teaching the essential elements of the Periodic Table
Keywords: Alfabetização científica; Ludicidade; Ensino fundamental; Scientific literacy; Playfulness; Elementary education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade